Implementasi Manajemen Perkantoran Dalam Meningkatkan Administrasi Siswa Di Mts Laboratorium UINSU - Sukmawan, Indah; Lubis, Artika; Damanik, Nazla Khairunnisa; Darajah, Zakiyah; Darmansah, Tengku (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the implementation of office management in improving the quality of student administration at MTs Laboratorium UINSU. Office management is an essential element in supporting the smooth operation of administrative processes, including student data management, correspondence, and information services. This research employs a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the application of office management principles—such as work planning, task organization, supervision of administrative activities, and the use of information technology—can enhance the efficiency and accuracy of student administrative management. Therefore, effective implementation of office management has a positive impact on student administrative services at MTs Laboratorium UINSU.